EFEKTIVITAS PELAKSANAAN PROGRAM KAMPUNG KELUARGA BERENCANA (KB) KOTA PEKANBARU - Anggraini, Tiara; Mashur, Dadang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Kampung KB Program is a Government Program in the framework of contorlling population and familly planning in order to succeed the development priority agenda (Nawacita) in point number three "Building Indonesia from the Fringe by Strengthening Regions and Villages in the Unitary State Framework" and point number five "Improving the Quality of Indonesian Human Life" through Population and Family Planning Development which is mandated by the President of the Republic of Indonesia. This study aims to get an overview of community empowerment through the Kampung KB Program of  Pekanbaru City which was socialized through Dinas Pengendalian Kependudukan dan Keluarga Berencana of Pekanbaru city. The concept theory used of this research is Effectiveness concept Mahmudi (2015:86) by enacting the concept theory Effectiveness is input, output, process,and outcome. Qualitative method is used in this research by using purposive sampling technique in which data collection technique covers : interview, observation, documentary, literature study. The results of this research that generally, community empowerment through a Kampung KB Program of Pekanbaru City is still in the devolopmental phase seen from still fount some circles who do not know Kampung KB Program. Community Empowewment through Kampung KB program is influenced by several factors is lack of commitment, especially for local officials, and program socialization so that everyone understands the overall planning of the village family planning.  Keywords : Effectiveness, Program, Kampung KB